2019
DOI: 10.1021/acs.iecr.9b04994
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization-Resistant Carboxyl-Functionalized 6FDA-Polyimide of Intrinsic Microporosity (PIM–PI) for Membrane-Based Gas Separation

Abstract: A novel trimethyl-substituted carboxyl-containing polyimide was synthesized by a one-pot high temperature polycondensation reaction of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) and 3,5-diamino-2,4,6-trimethylbenzoic acid (TrMCA). The polyimide (6FDA-TrMCA) displayed Brunauer-Emmett-Teller (BET) surface area of 260 m 2 g-1 demonstrating intrinsic microporosity in contrast to the related low-free volume COOH-functionalized polyimide 6FDA-DABA. Compared to the non-functionalized 6FDA polyimide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 44 publications
2
66
0
Order By: Relevance
“…As expected, the T g of 6FDA-DAM:DABApolyimide determined by DSC show an obvious increase from 357 8 8Ct o3 75 8 8Ca st he DAM:DABA Angewandte ratio increases from 1:2t o3:2 (Figure 1b,d), indicating that incorporating more DAMmoiety in the polyimide backbone increases the polyimide chain rigidity.T his is due to the presence of bulky methyl groups in DAMmoiety that inhibit localized, rotational mobilities of polymer backbone.S uch rigid backbones of 6FDA-DAM:DABAp olyimides with more DAMm oieties lead to higher packing resistance and suppresses the polymer chain packing in the formed membranes,thus leading to high free volume within the membrane matrix. [12] In addition, previous work [13] demonstrated that carboxyl groups in polyimide can form hydrogen bonds with the carbonyl and imide groups of adjacent polyimide chains. In this case,i tc an tighten chain packing and reduce free volume of the membrane when more DABA is incorporated in the polymer backbone.W ide angle X-ray diffraction (WAXD) measurements were performed and d-spacings of 6FDA-DAM:DABAp olyimide membranes,w hich can be used as an indicator of polymer chain packing in dense films, were calculated using Braggsl aw.R esults represented in Figure 1c Thed-spacings of 6FDA-DAM and 6FDA-DABAp olyimides reported in previous study [14] are shown here for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the T g of 6FDA-DAM:DABApolyimide determined by DSC show an obvious increase from 357 8 8Ct o3 75 8 8Ca st he DAM:DABA Angewandte ratio increases from 1:2t o3:2 (Figure 1b,d), indicating that incorporating more DAMmoiety in the polyimide backbone increases the polyimide chain rigidity.T his is due to the presence of bulky methyl groups in DAMmoiety that inhibit localized, rotational mobilities of polymer backbone.S uch rigid backbones of 6FDA-DAM:DABAp olyimides with more DAMm oieties lead to higher packing resistance and suppresses the polymer chain packing in the formed membranes,thus leading to high free volume within the membrane matrix. [12] In addition, previous work [13] demonstrated that carboxyl groups in polyimide can form hydrogen bonds with the carbonyl and imide groups of adjacent polyimide chains. In this case,i tc an tighten chain packing and reduce free volume of the membrane when more DABA is incorporated in the polymer backbone.W ide angle X-ray diffraction (WAXD) measurements were performed and d-spacings of 6FDA-DAM:DABAp olyimide membranes,w hich can be used as an indicator of polymer chain packing in dense films, were calculated using Braggsl aw.R esults represented in Figure 1c Thed-spacings of 6FDA-DAM and 6FDA-DABAp olyimides reported in previous study [14] are shown here for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorinated porous polyimide polymer was synthesized by reacting 6FDA (0.59 g, 1.33 mmol) with TrMPD (0.2 g, 1.33 mmol) in m-cresol (3 mL) in a 25 mL Schlenk tube equipped with a mechanical stirrer, a nitrogen inlet and an oil bubbler (Scheme 1). 27 The solution was heated to 80°C and isoquinoline (0.1 mL) was added under nitrogen, followed by stirring at 200°C for 4 h. Dry nitrogen stream was used to remove water, which resulted from the conversion of polyamic acid to polyimide. The viscous solution was cooled and poured into methanol, resulting in the precipitation of the polymer in a fibrous form, which was collected by filtration and purified twice by re-precipitation from solutions of N,N-dimethylformamide (DMF) into methanol.…”
Section: Synthesis Of the Fluorinated Porous Polyimidementioning
confidence: 99%
“…36,37 Thus, RP-COOH shows higher CO2 sorption over the full range of pressure than RP-CN (Figure 4d), enhancing the permeability of the RP-COOH membrane. The slight drop of H2 permeability maybe contributed by the lower fractional free volume and tighter average chain spacing after carboxyl functionalization in RP-COOH, 39 evidenced by PALS study (Figure 4e).…”
Section: Resultsmentioning
confidence: 89%